DUBR non-coding RNA regulates gene expression by affecting AP-1 enhancer accessibility - Simone D. Hall; Khoa Tran; Jonathan Zhu; Tong Su; Colleen A. McHugh (Functional & Integrative Genomics, 2025)
Non-coding RNAs (ncRNAs) are finely tuned cellular regulators important for human cell growth and cancer progression. DUBR ( Dppa2 upstream binding RNA, also known as linc00883) is a nuclear ncRNA first discovered in mice for its role in regulating myoblast differentiation through interactions with chromatin and DNA methyltransferases. High expression levels of this ncRNA are predictive of poor patient outcome in colon adenocarcinoma, suggesting that DUBR may be involved in controlling cancer growth. To elucidate its function, we used RAP-MS and RNA immunoprecipitation techniques which revealed its interaction with epigenetic maintenance proteins in the human colon cancer cell line HCT116. Further, ATAC-seq and RNA-seq were used to address its function in regulating the epigenome and transcriptome of HCT116 cells. Here we report that DUBR is a regulator of human colon cancer cell line HCT116 survival. Additionally, we find that the ncRNA DUBR regulates AP-1 transcription factor binding site accessibility at enhancers of genes involved in differentiation and morphogenesis through interactions with epigenetic proteins such as NuRD complex members HDAC1 and CHD4.